The Intersection of Religion and Art: Comparative Analysis of Hindu and Buddhist Iconography (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2023)
This paper delves into the fascinating realm where religion and art converge, focusing on the rich tapestry of Hindu and Buddhist iconography. Through a comparative lens, it explores the intricate symbiosis between these two ancient traditions, examining how their unique artistic expressions serve as visual narratives of profound philosophical and spiritual concepts. Drawing from a diverse array of historical and contemporary sources, the study begins by elucidating the foundational principles underlying Hindu and Buddhist worldviews. It then embarks on a journey through the realms of visual representation, meticulously dissecting the symbolism embedded within their respective iconographic traditions. Central to this exploration is an analysis of key themes such as cosmology, deity worship, and the depiction of sacred narratives.